2014
DOI: 10.4103/2141-9248.133462
|View full text |Cite
|
Sign up to set email alerts
|

Histopathological profile of breast cancer in an African population

Abstract: Background:Currently breast cancer (BRCA) still remain the most commonly diagnosed female cancer globally with a significant geographic, racial and ethnical variations in its incidence.Aim:This article examines the frequency and histological types and grades of BRCA in a pioneer teaching Hospital in Delta State, Nigeria.Materials and Methods:H and E stained-slides of breast biopsies diagnosed at the Central Hospital, Warri from 2005 to 2011 were archived and studied. Request forms were scrutinized for clinical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
10
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 15 publications
6
10
2
Order By: Relevance
“…This is consistent with findings in Africa, Europe and the world at large for the most frequently diagnosed breast cancer type [14, 15]. The fact that a considerable amount of records we retrieved were diagnosed or concluded only as either “adenocarcinoma” or “breast malignancy”, may explain why we observed less IDC compared to the documented 70–88% elsewhere [1618]. More ancillary diagnostic techniques or better tissue harvest may be necessitated to counter this.…”
Section: Discussionsupporting
confidence: 91%
“…This is consistent with findings in Africa, Europe and the world at large for the most frequently diagnosed breast cancer type [14, 15]. The fact that a considerable amount of records we retrieved were diagnosed or concluded only as either “adenocarcinoma” or “breast malignancy”, may explain why we observed less IDC compared to the documented 70–88% elsewhere [1618]. More ancillary diagnostic techniques or better tissue harvest may be necessitated to counter this.…”
Section: Discussionsupporting
confidence: 91%
“…At the national level, only the South-West, South-South and North-Central Nigeria had cases of Paget's disease. Its prevalence in Ogun State (South-West) was higher than that recorded in Delta State (South-South) [13] but lower than that reported in Benue State, North-Central [15]. The prevalence of medullary carcinoma in this study was higher than that reported in Maiduguri [18] and Warri [13] but lower than that reported in Lagos [10], Benin [14] and Zaria [20].…”
Section: Discussioncontrasting
confidence: 73%
“…This suggests that individuals in Ogun State are at low risk of developing medullary carcinoma than its neighbouring South-West State (Lagos State).. Mucinous Carcinoma is a mucin containing breast cancer surrounded by tumor cells [36]. Our study showed low prevalence of mucinous carcinoma in Ogun State compared with that found in other States in Nigeria [10,11,[13][14][15]18,20].…”
Section: Discussionmentioning
confidence: 52%
See 2 more Smart Citations